Grass-legume mixtures for enhanced forage production: analysis of dry matter yield and competition indices - Baba, Mohamed; Abd Halim, Mohd Ridzwan; Alimon, Abdul Razak; Abu Bakar, Idris (Academic Journals, 2011)
A six months field trial was conducted at the University Putra, Malaysia to evaluate dry matter yield and nature of competition between Panicum maximum (guinea grass) and each of the following legumes; Stylosanthes guianensis (stylo), Macroptillium bracteatum (burgundy bean), Arachis pintoi, and Centrosema pubescens (centro) in accordance with DeWit (1960) replacement principle. There were 20 treatments in all consisting of monocultures of grass, legume and grass-legume mixtures in the ratios 4:0, 3:1, 2:2, 1:3 and 0:4. The competition indices employed were relative yield total (RYT), relative crowding coefficient (RCC) or (k) and aggresivity index (AI). Guinea-stylo, guinea-Arachis and guineaburgundy mixtures, irrespective of ratio combination, showed lower total dry matter yields than their respective grass monocultures. Guinea-centro (2:2) and guinea-centro (3:1), on the other hand, gave higher total dry matter yields (14.52 and 13.82 tons/ha), respectively than their grass monocultures. No significant differences were observed among mixtures; however, monocultures of legumes produced significantly lower yields (p < 0.05) than those of grass and mixtures. All mixtures recorded mean RYT values of greater than one (1). Guinea-stylo (GS 2:2) and guinea centro (GC 2:2) had the highest RYT values of 1.41 and 1.40 respectively. Mean k values of grasses in mixtures were higher than those of legumes except in guinea-stylo (GS 1:3) and guinea- Arachis (GA 1:3). Mean aggressivity index suggests that legumes were generally more aggressive at 1:3 grass-legume mixture combination, while grass gained the upper hand at 2:2 and 3:1 grass-legume proportion. Guinea-centro (GC 2:2) was recommended as the most compatible combination.